POLICY ANALYSIS ON INSTITUTIONALIZATION OF HOUSING AND REGION SETTLEMENT - Mendra Wijaya; Tengku Fahrul Gafar (LPPM Universitas Abdurrab, 2019)
The distribution of government task is divided into two kinds, the absolute task performed by the central government; and concurrent task (the task of choice and mandatory) that are a joint task between the central and local governments. Based on Law Number 23 the Year 2014 on Regional Government, the task of housing and settlement area is a mandatory task (basic service) of the (central and local) government tasks. However, there is a policy change that states that providing housing is not only a government (central and local) task, but also requires the involvement of other government agencies associated with this task, thus have to create a separate unit of work in handling it. Therefore, this paper aims to identify and analyze various policies and institutional coordination in the field of Housing and Settlement Area with the approach of Law of Governance, then provide solutions to efforts in increasing the institutional capacity so as not to overlap.